2005
DOI: 10.1002/anie.200462531
|View full text |Cite
|
Sign up to set email alerts
|

Stable, Soluble Beryllium Aluminum Citrate Complexes Inspired by the Emerald Mineral Structure

Abstract: A gem of a structure: A mixed‐metal species with a structure very similar to the beryl structure found in nature is the 1:1:2 title complex (see structure). Its core structure contains a ring of alternating Al and Be atoms bridged by the aliphatic hydroxy group of the citric acid. A 1:1:1 complex isolated from phosphate buffer has a larger cluster structure consisting of six Al–Be–citrate species linked by bridging phosphate groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…It is clear that a carboxylic acid and an alcohol together are not sufficient for strong binding based on the results with DMCA and 3-hydroxypropanoic acid. These results combined with the 1:2 (CA:Be) ratio identified for CA and previous literature with similar binding motif [9,10] led us to the conclusion that Be O Be is the critical binding motif with the O coming from the central RO of CA and carboxylates bound to the ends of each Be.…”
Section: Ca Binding To Beryllium With a Be-o-be Linkagesupporting
confidence: 55%
See 2 more Smart Citations
“…It is clear that a carboxylic acid and an alcohol together are not sufficient for strong binding based on the results with DMCA and 3-hydroxypropanoic acid. These results combined with the 1:2 (CA:Be) ratio identified for CA and previous literature with similar binding motif [9,10] led us to the conclusion that Be O Be is the critical binding motif with the O coming from the central RO of CA and carboxylates bound to the ends of each Be.…”
Section: Ca Binding To Beryllium With a Be-o-be Linkagesupporting
confidence: 55%
“…A recent report has shown that a Be O Be motif is highly stable and selective for Be with the bridging O coming from a phenolate [9]. Also another recent report showing a Al/Be motif (A1 O Be) utilizing CA [10]. Theoretical studies also indicate the importance of the Be O Be unit [11].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…We recently investigated the interaction of CA with Be and Al and reported that the complex (NH 4 ) 6 [Be 2 Al 2 (CA) 4 ] was formed in quantitative yield by neutralizing an acidic solution containing Al(NO 3 ) 3 , Be(NO 3 ) 2 and citric acid with aqueous NH 3 . 32 The mixed metal complex is highly soluble in water (~3M) from pH 3.5 to 10.5. The 9 Be NMR spectrum exhibits one peak at 1.84 ppm indicating that the Be resides in the six-membered chelated ring of citrate and the 27 Al NMR spectrum shows a broad singlet at 14.0 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…The phosphate complex is highly soluble at pH 7 (>1 M), stable in the presence of phosphate media (0.5 M), and has been characterized by X-ray diffraction. 32 The Be-O-Al units are bridged by α-hydroxyl groups from the CA ligands as in the Be 2 Al 2 (CA) 4 complex, but the phosphate structure has a large cluster with six Be-O-Al units stitched together by phosphate groups. The structure is templated by two additional phosphate groups in the center of the molecule with each phosphate group binding three aluminiums with one unbound P-O free bond aligned on the C 3 axis of the molecule.…”
Section: Introductionmentioning
confidence: 99%